Using ELC Study Zone Website in Teaching Reading at Senior High School - Roysan Fariq; Jufri Jufri (Universitas Negeri Padang, 2018)
This paper describes the use of ELC Study Zone Website in teaching reading. The purpose of this paper is explaining how to use ELC Study Zone Website in increasing the ability and motivation of senior high school students in teaching reading. The main problem that students faces get diffulties in teaching reading low motivation of students in learning reading. As a teacher, they have to find some strategies or activities to solve this problem. One of the activities is using ELC Study Zone Website. ELC Study Zone Website is an educational website which serves a lot of materials, resources for English language such as, topics, reading text, interactive exercise, and some videos and audio to support in learning. It could make the students more understand, because all of the materials come from the native speaker. By the warm situations that have been created when using ELC Study Zone Website in teaching reading, the students could remove their shyness in reading and will be motivated to read in the learning process.